Influence of Air Duct Structure on the Flow Field and Temperature Field of Self-pickup Freezers - Chen Zhiming; Zhang Zhongbin; Xu Guanyi; Huang Hu; Wang Qing (Zhileng xuebao)
Modifying the air duct structure can effectively improve the air flow inside self-pickup freezers and optimize their thermal environment performance. Under the M-test package condition, air duct structures were modified separately with respect to axial baffle angle (30°, 45°, 60°, and 90°), perforation rate (6%, 8%, and 10%), and opening mode of the back orifice plate (non-uniform openings with upper sparse and lower dense, lower centralized openings, and equally spaced openings). Ten types of models were established and compared to determine the optimal structure model. Simulation results of the original structure (axial baffle angle of 45°, centralized openings, and perforation rate of 6%) were compared with the measured results to verify the correctness of the model. Both the numerical simulation and experimental verification show that the uniformity at α= 60° is 23% higher than that at 45°, velocity uniformity of non-uniform opening is 4.8% higher than that of the uniform openings, and overall uniformity is 5.1% higher than that of the original 6% when φ=8%. Therefore, airflow in the freezer is well organized and thermal environment performance is the best when the baffle angle of the axial fan was α=60°, non-uniform opening of the back orifice plate was considered, and perforation rate φ=8%.